Seroprevalence of HTLV-1/2 among blood donors in the state of Maranhão, Brazil - de Castro Viana, Graça Maria (Sociedade Brasileira de Hematologia e Hemoterapia, 2014)
BACKGROUND: Infection with human T-lymphotropic virus 1 or 2 (HTLV-1/2) is a major health problem. There is a public health policy defining measures for state hematology and hemotherapy centers in Brazil, in order to avoid virus transmission through blood donors. OBJECTIVE: This study aimed to evaluate the seroprevalence of HTLV-1/2 in blood donors in the State of Maranhão, Brazil, during routine blood unit screening. METHODS: Screening tests of blood donors using the enzyme-linked immunosorbent assay (ELISA) to detect seropositivity for HTLV-1/2 performed at the Hematology and Hemotherapy Center of the State of Maranhão (HEMOMAR) between July of 2003 and December of 2009 were retrospectively evaluated. RESULTS: Of the 365,564 blood donors, 561 (0.15%) were HTLV-1/2-positive, of whom 72 (12.8%) performed the confirmatory test (Western blot). In donors who had a confirmatory test, 53 (73.6%) were positive. The ages of the infected individuals ranged from 18 to 65 years; 305 (54%) were aged over 40 years. Among the infected individuals, 309 (55%) were male, 399 (71%) were mixed-race, and 259 (46%) were single. Co-infections were frequently found, especially with hepatitis B (in 68.6% of the cases). CONCLUSION: The results obtained will contribute to the planning and implementation of control measures by the epidemiological surveillance agency of Maranhão, and will also contribute to reducing morbidity. The high seropositivity in a small sample in donors who had confirmatory tests indicates the need for confirmatory tests for all donors who initially test as seropositive. © 2014 Associação Brasileira de Hematologia, Hemoterapia e Terapia Celular. All rights reserved.